THE EFFECTIVENESS OF PROBLEM-BASED LEARNING MODEL IN IMPROVING STUDENTS' UNDERSTANDING OF THE CONCEPT OF THE VALUES OF PANCASILA PRINCIPLES IN ELEMENTARY SCHOOL - Diki Riyadi; Mubarok Somantri; Ari Arasy Magistra (Universitas Islam Negeri Mataram, 2025)
This study was motivated by the low level of understanding of Phase B Grade III elementary school students in Pancasila education, particularly in the material on the meaning of the values of Pancasila. Preliminary studies suggest that some students struggle to comprehend the meaning and values of Pancasila. This study aims to measure the effectiveness of using the problem-based learning model in improving students' understanding of the values embodied in the Pancasila principles in elementary school. The research approach employed is a quantitative method, utilizing a pre-experimental design with a one-group pretest-posttest design. The sample in this study consists of 23 students in phase B at one elementary school in Sukajadi District, Bandung City. The instrument used is a written test with essay-type questions. The data analysis used includes normality tests, homogeneity tests, hypothesis tests, and N-Gain tests. The analysis results showed that the average post-test scores increased from the average pre-test scores, from 55.35 to 81.43. Based on the hypothesis test, the significance value was 0.001 < 0.05, so H0 was rejected and H1 was accepted, meaning that there was a significant improvement in conceptual understanding ability. Based on the N-Gain test, an N-Gain score of 0.5757 was obtained, meaning the N-Gain score falls under the “moderate” criterion. Meanwhile, the N-Gain percentage shows a value of 57.5673, which is greater than 55, indicating that the PBL learning model is sufficiently effective in enhancing students' conceptual understanding in Phase B of elementary school.